2016
DOI: 10.1007/s11695-016-2407-6
|View full text |Cite
|
Sign up to set email alerts
|

Results of Laparoscopic Sleeve Gastrectomy—5-Year Follow-Up Study in an Eastern European Emerging Bariatric Center

Abstract: LSG is a safe procedure, with low postoperative morbidity rates and excellent short-term %EWL results up to 3 years after surgery, including resolution or improvement of the main obesity-related comorbidities. The results were superior in the category of younger and lower initial BMI obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Taken together these results could suggest that ATM switch express GSH-R may have a pro-inflammatory phenotype. The immunohistochemical analysis could be a useful test to assess the macrophage functions and to predict the following development of obesity-associated metabolic complications [20][21][22][23][24][25][26][27].…”
Section: Immunohistochemistry Of CD 68 and Ghs-rmentioning
confidence: 99%
“…Taken together these results could suggest that ATM switch express GSH-R may have a pro-inflammatory phenotype. The immunohistochemical analysis could be a useful test to assess the macrophage functions and to predict the following development of obesity-associated metabolic complications [20][21][22][23][24][25][26][27].…”
Section: Immunohistochemistry Of CD 68 and Ghs-rmentioning
confidence: 99%
“…In a recently published meta-analysis comparing surgery with PAIR in 1721 patients, the latter has been shown to have fewer major (25.1% vs 7.9%) and minor (33.0% vs 13.1%) complications and fewer recurrence rates (6.3% vs 1.6%) [31]. This could be also correlated in some small degree with others results, including the latest interest of our group in a multidisciplinary approach on laparoscopic surger y and metabolic dysfunctions associated deficits [37][38][39][40][41][42], especially considering that percutaneous aspiration-injection-reaspiration of hepatic cystic echinococcosis can be indeed associated with a multitude of other manifestations [43].…”
Section: Resultsmentioning
confidence: 82%
“…One of the possible mechanisms which might explain a link between obesity and periodontitis includes liver disorders [34,35], the fact that the adipose tissue secretes pro-inflammatory cytokine which can be molecules that engages the pathogenesis of these diseases. The association between IMC and the tumour necrosis factorα (TNF-α) in the fluid of the gingival portion suggests that the TNF-á in this fluid is derived from the adipose tissue in the obese patients [36,37]. Moreover, it has been suggested that there is an increase in the serous level of interleukin 6 and resistin, both secreted as adipocytes and associated with periodontitis.…”
Section: Resultsmentioning
confidence: 99%